Self-Sovereign Identity in a Globalized World: Credentials-Based Identity Systems as a Driver for Economic Inclusion - Wang, Fennie; De Filippi, Primavera (Frontiers in Blockchain, 2020)
After introducing key concepts and definitions in the field of digital identity, this paper will investigate the benefits and drawbacks of existing identity systems on the road towards achieving self-sovereign identity. It will explore, in particular, the use of blockchain technology and biometrics as a means to ensure the “unicity” and “singularity” of identities, and the associated challenges pertaining to the security and confidentiality of personal information. The paper will then propose a model of blockchain-based self-sovereign identity based on attestations, claims, credentials and permissions, which is globally portable across the life of an individual. Such a system is not dependent on any particular government or organization for administration or legitimacy, although it might include government issued identification and biometrics as one of many indicia of identity. Such a solution based on a recorded and signed digital history of actions is a system that best approximates the fluidity and granularity of identity, enabling individuals to express only specific facets of their identity, depending on the parties with whom they wish to interact. This paper focuses on two case studies to explain how such a credentials system could work in specific contexts: (1) Kiva’s identity protocol for building credit history in Sierra Leone, and (2) World Food Programme’s Building Blocks program for delivering cash aid to refugees in Jordan. Finally, the paper will explore what the future might look like when blockchain-based cryptocurrencies and self-sovereign identity intersect. With digital transactions functioning as identity claims within an ecosystem based on self-sovereign identity, new business models might emerge, such as identity insurance schemes, along with the emergence of value-stable cryptocurrencies (“stablecoins”) functioning as local currencies.